Electronic nicotine delivery systems and/or electronic non-nicotine delivery systems for tobacco smoking cessation or reduction: a systematic review and meta-analysis. Issue 2 (23rd February 2017) - El Dib, Regina; Suzumura, Erica A; Akl, Elie A; Gomaa, Huda; Agarwal, Arnav; Chang, Yaping; Prasad, Manya; Ashoorion, Vahid; Heels-Ansdell, Diane; Maziak, Wasim; Guyatt, Gordon
Abstract : Objective: A systematic review and meta-analysis to investigate the impact of electronic nicotine delivery systems (ENDS) and/or electronic non-nicotine delivery systems (ENNDS) versus no smoking cessation aid, or alternative smoking cessation aids, in cigarette smokers on long-term tobacco use. Data sources: Searches of MEDLINE, EMBASE, PsycInfo, CINAHL, CENTRAL and Web of Science up to December 2015. Study selection: Randomised controlled trials (RCTs) and prospective cohort studies. Data extraction: Three pairs of reviewers independently screened potentially eligible articles, extracted data from included studies on populations, interventions and outcomes and assessed their risk of bias. We used the Grading of Recommendations Assessment, Development and Evaluation approach to rate overall certainty of the evidence by outcome. Data synthesis: Three randomised trials including 1007 participants and nine cohorts including 13 115 participants proved eligible. Results provided by only two RCTs suggest a possible increase in tobacco smoking cessation with ENDS in comparison with ENNDS (RR 2.03, 95% CI 0.94 to 4.38; p=0.07; I 2 =0%, risk difference (RD) 64/1000 over 6 to 12 months, low-certainty evidence). Results from cohort studies suggested a possible reduction in quit rates with use of ENDS compared with no use of ENDS (OR 0.74, 95% CI 0.55 to 1.00; p=0.051; I 2 =56%, very low certainty). Conclusions: There is very limited evidence regarding the impact of ENDS or ENNDS on tobacco smoking cessation, reduction or adverse effects: data from RCTs are of low certainty and observational studies of very low certainty. The limitations of the cohort studies led us to a rating of very low-certainty evidence from which no credible inferences can be drawn. Lack of usefulness with regard to address the question of e-cigarettes' efficacy on smoking reduction and cessation was largely due to poor reporting. This review underlines the need to conduct well-designed trials measuring biochemically validated outcomes and adverse effects.